Multi-peak negative differential resistance in silicene superlattice: Toward multi-valued silicene logic devices - Sattari-Esfahlan, S. M. (Journal of applied physics, 2018)
Negative differential resistance (NDR) in two dimensional materials has been the subject of strong interest for ultra-low power nanoelectronic applications. Here, we report NDR characteristics of silicene superlattice (SL) at low bias voltages. Transport process manipulated by miniband regime for low bias region and Wannier-Stark (WS) ladders regime with multi-peak NDR for higher bias windows. Local tunneling peaks rise from hybridization of Wannier-Stark rungs in certain bias voltages. The bias position of WS states crossings down shifted with increasing device dimension leading to red shifted NDR window and increases peak to valley ratio (PVR) values. The multiple NDR windows are represented by changing the size and the number of well/barriers in silicene SL. Maximum PVR of 8 obtained for device with low height barriers. Multi-peak NDR with same PVR values in very low bias regime can find key applications in multi-valued memories with low static power dissipation.